2010
DOI: 10.2136/sssaj2009.0225
|View full text |Cite
|
Sign up to set email alerts
|

Soil Enzyme Activity in a Mediterranean Forest after Six Years of Drought

Abstract: A 6-yr experiment in drought manipulation was conducted in a Quercus ilex L. Mediterranean forest to simulate the drought conditions projected for the coming decades. We investigated the eff ects of those drought conditions on soil urease, protease, and β-glucosidase activities and the changes in C and N stocks in soil, leaves, and leaf litter. Elimination of runoff and rainfall resulted in lower soil water content than in control soils in autumn, winter, and spring (27, 61, and 53%, respectively). In soils su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 51 publications
5
45
0
Order By: Relevance
“…Water availability was not only associated with shifts in nutrient concentrations but also with their allocation to different organs [41,44], the stoichiometric relationships among the main nutrients [41,44,45] and the distribution of nutrients between plant and soil [43,[45][46][47]. Drought tends to decrease total nutrient contents in plant-soil systems, mainly in plants, that transfer nutrients from above-to belowground biomass and from plant to soil [44,48]. This modification of the biogeochemical cycles of the plant-soil system in response to environmental changes constitute a first step towards an altered flow of matter and nutrients through the trophic chain [38].…”
Section: Responses At the Molecular Level And In The Use Of Chemical mentioning
confidence: 99%
See 2 more Smart Citations
“…Water availability was not only associated with shifts in nutrient concentrations but also with their allocation to different organs [41,44], the stoichiometric relationships among the main nutrients [41,44,45] and the distribution of nutrients between plant and soil [43,[45][46][47]. Drought tends to decrease total nutrient contents in plant-soil systems, mainly in plants, that transfer nutrients from above-to belowground biomass and from plant to soil [44,48]. This modification of the biogeochemical cycles of the plant-soil system in response to environmental changes constitute a first step towards an altered flow of matter and nutrients through the trophic chain [38].…”
Section: Responses At the Molecular Level And In The Use Of Chemical mentioning
confidence: 99%
“…Drought also induced changes in the allocation of N to roots, probably to help meet the increased need for water [133]. Field experiments simulating climate change have demonstrated that drought has large impacts on soil traits, particularly C and nutrient status [48,134,135]. These experiments have found that soil respiration and the activities of soil and rhizospheric enzymes have been strongly and negatively affected by drought [48,134,135].…”
Section: Biogeochemical and Ecosystem Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…1). These effects are due most frequently to the decrease in soil moisture (Sardans et al, 2008a;Sardans and Peñuelas, 2010) but also to decreases in food quality and the nutrient contents of leaves and litter (Sardans et al, 2008d;Matías et al, 2011). These effects frequently lead to increases in recalcitrant forms of soil nutrients and decreases in forms available to plants (Sardans and Peñuelas, 2004;Sardans et al, 2006Sardans et al, , 2008d.…”
Section: Effects On the Availability And Stoichiometry Of Nutrients Amentioning
confidence: 99%
“…At the same time, desiccation tolerance mechanisms could trade off against other aspects of physiology (Raven, 1985;Schimel et al, 2007). For example, microbial taxa that survive better under drought might have lower growth efficiency due to increased metabolic costs (Killham and Firestone, 1984a) or fewer resources to invest in enzymatic machinery (Sardans and Peñuelas, 2010).…”
Section: Introductionmentioning
confidence: 99%